KEMITRAAN ANTARA BANK BCA DENGAN YAYASAN BENIH BAIK DALAM IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (STUDI KASUS PADA PROGRAM BAKTI CSR BANK BCA DALAM UPAYA MENINGKATKAN JUMLAH ALAT PELINDUNG DIRI TENAGA MEDIS) - Muhammad Riefky Setiawan, (2021)
Corporate Social Responsibility is one of the Public Relations activities to establish good relations with external stakeholders, namely the community around the company. Corporate Social Responsibility activities focus on a company that has a relationship to partner with an institution or organization and involve the surrounding community to participate in carrying out these CSR activities. This study aims to determine the process and implementation carried out between PT. Bank BCA with the Benih Baik.com Foundation in an effort to improve personal protective equipment for medical personnel due to the difficulty of the Covid-19 pandemic. The theory used in this research is Legitimacy Theory. Data collection techniques were carried out by means of interviews, and literature studies because direct observations were not usually carried out with current conditions. From this research, researchers seek information from several informants. Data analysis techniques used in this study were data collection, data reduction, data presentation, conclusions and verification. Researchers used data triangulation techniques in checking the validity of the data. Therefore, it can be seen and concluded that the CSR program process in the Bank BCA program here empowers MSMEs so that the economic cycle can run during this pandemic.